Pengaruh Pemanfaatan Media Audio Visual Terhadap Pembelajaran di MTsN 3 Kabupaten Aceh Barat - Aisya Zaskia (Indonesian Journal of Teaching and Teacher Education, 2022)
The purpose of this study was to determine the effect of using audio-visual media on learning at MTsN 3 Aceh Barat. The method that researchers use in this study is a quantitative method. Data collection methods used are interview methods, observation methods, questionnaire methods and documentation methods. The number of samples was 2 classes, namely class 8c and 8e, which were taken using the Proportionate Stratified Random Sampling technique. The hypothesis in this study (H0) is that the use of audio-visual media affects learning at MTsN 3 in West Aceh. While the hypothesis (H1) is the use of audio-visual media does not affect learning at MTsN 3 in West Aceh. Based on the results of the research, the correlation coefficient on the results above shows 0.673 or is negative so that the relationship between the variables is in a different direction. This can be interpreted that the audio-visual media factor will not affect the learning conditions at MTsN 3 Aceh Barat. With a significance of 0.673> 0.05 that audio-visual media has no significant relationship with learning conditions at MTsN 3 Aceh Barat.